Enhancement in critical current density and irreversibility field of bulk MgB2 by C and CaCO3 co-addition - Tan, Kean Sheng; Chen, Soo Kien; Jun, B. H.; Kim, C. J. (Institute of Physics, 2008)
Paper ash, a source of C and CaCO3, was used for the first time as a cheap form of sub-micron particles for doping. 0–10 wt% of the ash was added to Mg + 2B and in situ reacted at 850 ◦C for 30 min in flowing Ar atmosphere. The CaCO3 decomposed and reacted with B to form CaB6 as an impurity phase. Also, the Tc and the a-axis lattice parameter decreased with increasing ash content, which suggests that C substitution at boron sites occurred. Enhancement of high-field Jc(H), Hirr(T ) and Hc2(T ) was observed with an optimum level of about 5 wt% ash addition